2014
DOI: 10.1021/ja5045488
|View full text |Cite
|
Sign up to set email alerts
|

An Exceptionally Fast Homogeneous Carbon-Free Cobalt-Based Water Oxidation Catalyst

Abstract: An all-inorganic, oxidatively and thermally stable, homogeneous water oxidation catalyst based on redox-active (vanadate(V)-centered) polyoxometalate ligands, Na10[Co4(H2O)2(VW9O34)2]·35H2O (Na101-V2, sodium salt of the polyanion 1-V2), was synthesized, thoroughly characterized and shown to catalyze water oxidation in dark and visible-light-driven conditions. This synthetic catalyst is exceptionally fast under mild conditions (TOF > 1 × 10(3) s(-1)). Under light-driven conditions using [Ru(bpy)3](2+) as a phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
259
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(271 citation statements)
references
References 56 publications
(74 reference statements)
10
259
1
1
Order By: Relevance
“…As shown in Figure 3, there is no shift in the peak positions of the characteristic Zr1-WD2 resonances (at −9.33 and −13.94 ppm) in the presence of HSA, indicating the stability of the POM upon interaction with the protein. It should not be surprising that these polyoxotungstates are stable as this was already previously demonstrated by various techniques [63][64][65]. In addition, the slight decrease in the intensity of the POM peaks can be correlated with the formation of a large molecular complex with HSA which has a longer correlation time and thus a faster relaxation.…”
Section: Polyoxometalate Stability In the Presence Of Hsasupporting
confidence: 57%
“…As shown in Figure 3, there is no shift in the peak positions of the characteristic Zr1-WD2 resonances (at −9.33 and −13.94 ppm) in the presence of HSA, indicating the stability of the POM upon interaction with the protein. It should not be surprising that these polyoxotungstates are stable as this was already previously demonstrated by various techniques [63][64][65]. In addition, the slight decrease in the intensity of the POM peaks can be correlated with the formation of a large molecular complex with HSA which has a longer correlation time and thus a faster relaxation.…”
Section: Polyoxometalate Stability In the Presence Of Hsasupporting
confidence: 57%
“…In recent years, substantial progress has been reported on molecular water oxidation catalysts 1,2 although light driven water oxidation activity has been demonstrated in only a small number of cases. 3,4,5,6,7,8,9,10,11 Furthermore for these photoactivated systems, analyses of the different kinetics processes that determine system efficiency have been very limited to date and in several cases the molecular catalyst has been reported to degrade to the corresponding oxide. 3,6b,7,8,9a .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hill and co-workers have reported that cobalt-based polyoxometalates can be used as efficient light-driven carbon-free molecular catalysts for water oxidation [13,14]. As far as we known, very few reports describe the visible-light-driven H 2 evolution from water splitting using carbon-free homogeneous catalysts based on earth-abundant elements [12,15].…”
Section: Introductionmentioning
confidence: 99%